Content of polyphenolic compounds in Melilotus officinalis ecotypes from Morocco - Ayadi M.; Lahkim Bennani M.; Aarab A.; Brigui J.; Benicha M. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Twenty ecotypes of yellow Melilotus officinalis from the north-west pastures of Morocco have been cultivated in the experimental station of the National Institute of Agronomic Research of Tangier. The samples were collected during the vegetative, budding and flowering stages in order to evaluate the phenolic content. Phenolic content of the ecotypes collection varied significantly with the maturation stage and the ecotype origin. Total phenols (TP) increased significantly from 2.14% dry mater (DM) at the vegetative stage to 2.37% DM at the flowering stage (P<0.01). Total tannins (TT) increased from 0.71 % DM at vegetative stahe to 0.78% DM at the budding stage and then decreased to 0.67% DM in the flowering stage. In contrast, the condensed tannins content (CT) of the collection decreased significantly from 0.10 at the vegetative stateto 0.04% DM (P<0.001) at the flowering maturation stage. In addition, the content of TP and TT varied significantly between ecotypes, from 2.01 to 2.69 % DM (P<0.001) and from 0.44 to 1.15% DM (P<0.001), respectively. The high content of CT was obtained at the vegetative stage with 0.10% DM.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)